An Investigation on the Reasons For The Exclusion of Women in the Labor Market in Türkiye - Taşar, İzzet; Namlı, Şeydanur (Fırat University, 2023)
In order to achieve economic growth and development, all production factors must be used with maximum efficiency. Labor, which is one of the factors of production, is called labor in the market. In order to ensure full efficiency in the labor market, the labor force participation rate must be balanced. The distribution of the workforce in Türkiye is against women. For the purpose of this study, the labor market is analyzed according to gender distribution in order to ensure balanced distribution of the workforce and maximum benefit from production factors. Women's participation in the workforce were and popular barriers are examined in this study. While analyzing the labor force in the research, it was examined in two separate groups as men and women. The reasons for not participating in the labor force were evaluated with the comparison of the classical school, neoclassical school, Marxist school and feminist theory. The study consists of two main parts. In the first chapter, theoretical information about the female workforce was examined, the perspective of economics schools on the female workforce was stated, and a literature review examining the female workforce was conducted. In the second part It is the non-participation rate of women and individuals by converting the data of the Turkish Statistical Institute (TUIK) into tables and graphs. In the research, social opinion regarding women's participation in the labor market was evaluated by categorizing it with 'local survey' studies obtained from TÜİK. The 'reasons for not participating' created by TÜİK are detailed under sub-headings. As a result of the study, it was concluded that the data in Türkiye are compatible with the discrimination theory of the neoclassical school. A policy recommendation was made by making a comparison with countries in the European Union where women's participation in the workforce is high.

Ekonomik büyüme ve kalkınmanın sağlanabilmesi için üretim faktörlerinin tamamını maksimum verimle kullanılması gerekmektedir. Üretim faktörlerinden biri olan emek, piyasada işgücü olarak adlandırılmaktadır. İşgücü piyasasında tam verim sağlanabilmesi için dengeli bir işgücü katılım oranı olması gerekmektedir. Türkiye’de işgücünün kadın-erkek dağılımında kadınların aleyhinde bir dağılımı olduğu görülmektedir. Bu çalışma amacı dahilinde işgücünün dengeli dağılımını sağlayabilmek ve üretim faktörlerinin maksimum kullanımı için işgücü piyasasını cinsiyet dağılımına göre incelemektedir. Kadınların işgücüne katılmama nedenleri ve kadınların işgücünde katılma/katılmama durumunda oluşan algılar incelenmiştir. Çalışmada işgücü analiz edilirken kadın ve erkek olarak iki ayrı grupta incelenmiştir. İşgücüne katılmama nedenleri klasik okul, neoklasik okul, marksist okul ve feminist kuram görüşleriyle değerlendirilerek bu durumun iktisat teorisindeki yerine vurgu yapılmıştır. Yapılan çalışma 2 ana bölümden oluşmaktadır. Birinci bölümde kadın işgücüyle ilgili teorik bilgiler incelenmiş, iktisat okullarının kadın işgücüne bakış açısı belirtilerek, kadın işgücünü inceleyen literatür taraması yapılmıştır. İkinci kısımda ise Türkiye İstatistik Kurumu (TÜİK) verileri tablo ve grafik haline getirilerek kadın ve erkeklerin işgücüne katılmama nedenleri incelenmiştir. TÜİK’ den alınan ‘aile içi anket’ çalışmalarıyla kadının işgücü piyasasına katılımıyla ilgili toplumsal görüş sınıflandırılarak çalışma içerisinde değerlendirilmiştir. TÜİK’in oluşturduğu ‘katılmama nedenleri’ alt başlıklara ayrılarak detaylandırılmıştır. Çalışmanın sonucunda Türkiye’deki verilerin neoklasik okulun ayrımcılık teorisine uygun olduğu sonucuna ulaşılmıştır. Avrupa Birliği’nde yer alan ve kadın işgücü katılımının yüksek olduğu ülkelerle karşılaştırma yapılarak politika önerisinde bulunulmuştur.
TÜRKİYE’DE KADINLARIN İŞGÜCÜ PİYASASINA DAHİL OLMAMA NEDENLERİNİN İNCELENMESİ
Keywords: Employment; İstihdam